2020
DOI: 10.1186/s40645-019-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of high-resolution downscaling experiments for assessing strong wind hazard at local scales in complex terrain: a case study of Typhoon Songda (2004)

Abstract: This study investigated the representation of surface winds in complex terrain during the passage of Typhoon Sondga (2004) in downscaling simulations with the horizontal grid spacing of 200 m. The mountainous areas in Hokkaido where forest damages occurred in the typhoon event were chosen for the present analysis. The 200 m grid simulations were compared with the simulations with the grid spacing of 1 km. The 200 m grid simulations clearly indicated more enhanced and more frequent extremes both in the stronger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Yamada et al (2021) present a study focusing on the survival rate of typhoon "seeds" until they develop into typhoons using global data from High-ResMIP (Haarsma et al 2016), a collection of relatively high-resolution models among the CMIP6 models. Takemi and Ito (2020), on the other hand, perform a case study using a regional model and show that in complex terrain, improvements could be expected with higher resolutions down to the level of several hundred meters.…”
mentioning
confidence: 99%
“…Yamada et al (2021) present a study focusing on the survival rate of typhoon "seeds" until they develop into typhoons using global data from High-ResMIP (Haarsma et al 2016), a collection of relatively high-resolution models among the CMIP6 models. Takemi and Ito (2020), on the other hand, perform a case study using a regional model and show that in complex terrain, improvements could be expected with higher resolutions down to the level of several hundred meters.…”
mentioning
confidence: 99%
“…Takemi (2018) used a horizontal grid spacing of 167 m to simulate the heavy rainfall event that occurred in the northern part of Kyushu Island in July 2017 and indicated that the 167-m grid simulation quantitatively captured the rainfall amount. Takemi and Ito (2020) examined the ability to represent strong winds due to typhoons in complex terrain with a horizontal grid spacing of 200 m and indicated that the wind speeds simulated with a grid spacing of 200 m were quantitatively estimated better than those simulated with a grid spacing of 1 km. In this way, both studies demonstrated that the grid spacing on the order of 100 m adequately captured the spatial and temporal variability of rainfall and wind in complex terrain.…”
Section: Preparing the Dataset For Modelling 10mentioning
confidence: 99%
“…This technique has a variety of applications (Castro et al, 2005;Rockel, 2015), including local or regional climate change assessment (e.g., Barredo et al, 2020;Komurcu et al, 2018;Mathis et al, 2013;Xue et al, 2014). The finer mesh of the RCMs allows for a better resolved orography or local gradients (e.g., Cabos et al, 2019;Pontoppidan et al, 2017;Rummukainen, 2016;Takemi and Ito, 2020;Tiwari et al, 2014;Xu et al, 2018). Also, the importance of using high-spatial resolution RCMs for regional analyses based on momenta beyond mean values is shown in the literature (e.g., Domínguez et al, 2013;Gómez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%